Nursing care for patients with COVID-19 in the Intensive Care Unit: an integrative review (Research, Society and Development, 2023)
Objective: To analyze, based on the literature, the nursing care of patients with COVID-19 in the intensive care unit. Methodology: This is an integrative literature review, carried out by searching for studies in three databases. national and international data: Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrievel System Online (MEDLINE). The final sample consisted of 15 published studies. Results and Discussion: After crossing the descriptors and applicability of the inclusion and exclusion criteria, the discussion was based on 15 articles. Conclusion: Nursing provides care from the provision of oxygen therapy, cardiac monitoring, care with renal function, in addition to emotional support from the use of technologies and musicalization. The challenges related to the scarcity of material and human resources were highlighted, but nursing stood out with flexible and innovative care with a view to practices based on systematization and the nursing process.